THE SOLUTION OF DIFFERENTIAL EQUATION OF PHYSICAL PROBLEM BY THE USE OF MATLAB - FECHOVA, Erika (Trends in education, 2008)
At the present time teachers try to introduce and use information technologies in educational process of technical subjects at schools as mathematics, physics, chemistry. Apart from e-learning support (electronic materials and textbooks available on the internet), there are various mathematical software environments as MATLAB, Mathematica, MS Excel etc. The paper points out the possibility of MATLAB utilization at solving differential equation of physical problem.
Keywords: mathematical modelling; physical problem; differential equation; MATLAB